2017
DOI: 10.18632/oncotarget.15456
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil count is associated with myeloid derived suppressor cell level and presents prognostic value for hepatocellular carcinoma patients

Abstract: Myeloid Derived Suppressor Cell (MDSC) has been raised to be a novel target for multiple cancers. However, target agents on MDSC have not display promising efficacy. One of the critical reasons shall be less optimal patient selection. In the present study, we aimed to identify clinical parameters relevant to MDSC level in hepatocellular carcinoma (HCC) patients for future MDSC targeted therapy. In the present study, a series of 55 HCC patients (testing group) and 20 healthy donors were analyzed investigating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…Multivariate analysis showed that monocytes significantly related with MDSCs. A similar result has been found in a previous report [23]. These data suggest that MDSC level was associated with systemic inflammation in HCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Multivariate analysis showed that monocytes significantly related with MDSCs. A similar result has been found in a previous report [23]. These data suggest that MDSC level was associated with systemic inflammation in HCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…reported that MDSC appeared at late stage of carcinogenesis in murine HCC model which mimicked human diseases 17 . Clinically, it was reported that the population of MDSC in PBMC of HCC patients was much higher than in healthy normal control and non-tumor cirrhotic patients 20,24 . This study showed that the frequency of MDSC in peripheral blood could be quantitatively estimated according to the equation between the frequency of MDSC and tumor volumes.…”
Section: Discussionmentioning
confidence: 95%
“…NLR expresses the balance between the inflammatory and immune systems, making it a useful index that reflects systemic inflammatory responses 13. Our previous study indicated that elevation of neutrophils was associated with myeloid-derived suppressor cell (MDSC),29 which is a critical inducer of immune suppression in cancer. Other studies found that the increased neutrophil levels are related to a systemic release of chemokines and ILs, including vascular endothelial growth factor30 and angiopoietin-1 31.…”
Section: Discussionmentioning
confidence: 99%